1993
DOI: 10.1007/bf01877424
|View full text |Cite
|
Sign up to set email alerts
|

Free versus liposome-encapsulated muramyl tripeptide phosphatidylethanolamide (MTPPE) and interferon-y (IFN-y) in experimental infection with Listeria Monocytogenes

Abstract: The effect of free and liposome-encapsulated muramyl tripeptide phosphatidylethanolamide (MTPPE) and interferon-y (IFN-y) on the resistance against Listeria monocytogenes infection in mice was investigated. It was shown that administration of MTPPE or IFN-y at 24 h before bacterial inoculation led to increased resistance against L. monocytogenes infection in terms of a decrease in bacterial numbers in liver and spleen. Encapsulation of MTPPE and IFN-y in liposomes increased their efficacy 33- or 66-fold, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Administration of muramyl peptides cures lethal infections by bacteria, fungi, and parasites. These cures have been obtained with MDP in animal models given lethal infections with Klebsiella pneumoniae [20,100], Listeria monocytogenes [101], C. albicans [21], Trypanosoma cruzi [102,103], and Schistosoma mansoni [104]. Protection of mice from a lethal infection with C. albicans is shown in figure 7.…”
Section: Macrophage Activation In Animal Modelsmentioning
confidence: 99%
“…Administration of muramyl peptides cures lethal infections by bacteria, fungi, and parasites. These cures have been obtained with MDP in animal models given lethal infections with Klebsiella pneumoniae [20,100], Listeria monocytogenes [101], C. albicans [21], Trypanosoma cruzi [102,103], and Schistosoma mansoni [104]. Protection of mice from a lethal infection with C. albicans is shown in figure 7.…”
Section: Macrophage Activation In Animal Modelsmentioning
confidence: 99%
“…Tanguay et al (1994) found that L-MTP-PE administered alone activated peritoneal macrophages with lower intensity, but co-incubation of macrophages with L-MTP-PE and IFN-γ together has duplicated their cytotoxicity. An important role of IFN-γ in effect of the immunomodulator on macrophages infected with Listeria monocytogenes was also verified by Melissen et al (1993b). Ten Hagen et al (1998) underlined IFN-γ contribution to immunomodulative effect of L-MTP-PE in Klebsiella pneumoniae infection of mice and thus confirmed a key role of T cells in immunity boost of immunomodulated host organism.…”
Section: Discussionmentioning
confidence: 66%
“…As liposome-encapsuJated immunomodulators exert their action mainly via fixed macrophages, the first studies in this field were performed in intracellular infections of the cells of the MPS. It was demonstrated that liposome-encapsulated IFN 7 was more effective than the free agent in animal models of infection caused by Listeria monocytogenes [65] and Leishmania donovani [64]. These micro-organisms replicate primarily inside macrophages of the MPS.…”
Section: Liposome-mediated Delivery Of Immunomodulatorsmentioning
confidence: 99%
“…This may be accomplished by the administration of the immunomodulators co-encapsulated in the same liposome, which will result in simultaneous delivery of the agents to the target cell. Treatment of Listeria infection with MTP-PE and IFN T in the same liposome resulted in an enhanced antimicrobial resistance [65]. Synergism between liposomal MTP-PE and IFNTwas also shown in a Leishmania infection model [64] and in tumour models [70].…”
Section: Liposome-mediated Delivery Of Immunomodulatorsmentioning
confidence: 99%